Pengaruh Pendidikan Multikultural terhadap Karakter Siswa dan Kecakapan Berwirausaha Peserta Didik - Fathor Rakhman (Elementary Teacher Education Program, Majalengka University, 2023)
Education is an effort to equip students to have abilities that can benefit them in the life of society, nation and state. The diversity of cultures in Indonesia provides its own challenges in multicultural life, so concern and sensitivity to multicultural issues is needed. The purpose of this study was to determine the effect of multicultural education on student character and entrepreneurial skills. The technique in this study uses a survey-quantitative method to find the magnitude of the influence between variables. While the questionnaire is used as data collection. The influence between variables is proven by using the regression test. The results of this study indicate that there is a significant influence between multicultural education on student character and entrepreneurial skills.